Beginnings of Literary Images of a Lithuanian and Lithuania in Latvia - Butkus, Vigmantas (Acta humanitarica academiae Saulensis, 2021)
In Latvian literature since the second half of the 19th century, Lithuanians, Lithuania, its history, its particular sites are quite often depicted in some specific view, sometimes comprehensively, conceptually, sometimes episodically, passingly. The article attempts to demonstrate what image of Lithuanians and Lithuania that could have made an impact on Latvian literature, formed before it emerged and while emerging: in folklore, writings of Baltic Germans in the 18th–19th centuries and works by activists of the National Awakening. In Latvian folk songs, Lithuanians (leiši) are mostly depicted either as close, connected to Latvians by marital bonds, likely bonding people or as enemies, raiders to defend against. There are many other, random, hardly classified Lithuanian motifs in the discussed songs. In narrative folklore, the image of a Lithuanian is more one-sided and not very amiable: a Lithuanian person is usually portrayed in a mocking manner, emphasising negative traits, such as laziness, lack of intelligence, gullibility, etc. In texts by Baltic Germans, a Lithuanian of that period was also mostly characterised negatively, by emphasising one’s indolence, backwardness, ignorance. The image of Lithuania in the past, its rulers described by them is different: reserved, objectivised, including sometimes expressed nuances of surprise, respect towards the former geopolitical, military might of Lithuania. The old Lithuanian (and Prussian) religion, mythology started being treated as Latvian ones (Gotthard Friedrich Stender (1714–1796) and others), community of the Lithuanian, Old Prussian and Latvian languages, ethnoses was observed, even considering them all to be one nation (Carl Friedrich Watson (1777–1826) and others), history of Lithuania started being positively assessed and presented while bringing it closer to the history of Latvia (Garlieb Helwig Merkel, 1769–1850). Ideas of community or kinship of the Lithuanian and Latvian languages, religion, history were actively taken over and intensively fostered by the New Latvians (jaunlatvieši) and other activists of the Latvian National Awakening in the 19th century. They were writing on an inseparable history of Latvians and Lithuanians or even one nation, carried out in-depth investigation of the past and language of Lithuanians, both grounding on their data, objectively, reasonably and subjectively, motivelessly extending the concept of Latvian history, enriching the Latvian language. Atis Kronvalds (1837–1875), Juris Alunāns (born Gustavs Georgs Frīdrihs Alunāns, 1832–1864), Fridrihs Veinbergs (1844–1924), Andrejs Dīriķis (1853–1888) and other enlightened people were those whose endeavours contributed to making the image of Lithuanians and Lithuania in the public space of Latvia more positive, usually, while linking to the past, it was being idealised. Such, idealised, image was mostly taken over by Latvian romantic, neoromantic literature since the 19th century.